2013
DOI: 10.15835/nsb539120
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Metabolic Origins of Milk Fatty Acids

Abstract: Milk fat and its fatty acid profile are important determinants of the technological, sensorial, and nutritional properties of milk and dairy products. The two major processes contributing to the presence of fatty acids in ruminant milk are the mammary lipogenesis and the lipid metabolism in the rumen. Among fatty acids, 4:0 to 12:0, almost all 14:0 and about a half of 16:0 in milk fat derive from de novo synthesis within the mammary gland. De novo synthesis utilizes as precursors acetate and butyrate produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Research has shown that ruminant meat fatty acid profile can be influenced by different rations [34], such as the inclusion of rich PUFA sources in cattle diets [35]. Dietary lipids are subjected to lipolysis by rumen bacteria, which then hydrogenate and isomerize the PUFA included in the feed to more saturated end products [36,37]. At the same time metabolites such as rumenic acid (9 cis, 11 trans-18:2) or vaccenic acid (11 trans-18:1) are produced, which are consider to be beneficial for the consumer [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that ruminant meat fatty acid profile can be influenced by different rations [34], such as the inclusion of rich PUFA sources in cattle diets [35]. Dietary lipids are subjected to lipolysis by rumen bacteria, which then hydrogenate and isomerize the PUFA included in the feed to more saturated end products [36,37]. At the same time metabolites such as rumenic acid (9 cis, 11 trans-18:2) or vaccenic acid (11 trans-18:1) are produced, which are consider to be beneficial for the consumer [38].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the most common fatty acids, as well as SFA, MUFA, and PUFA did not differ significantly (P>0.050) between the three experiments groups, in contrast with the original hypothesis of the experiment. It is possible that since SSH unsaturated fatty acids are not protected, they are quickly saturated in the rumen, before being absorbed along the small intestine of the animal [36,37,40].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the results of metabolomics in our study revealed that the supplementation of inulin signi cantly downregulated the lipid metabolism in dairy cows. The increase in the ratio of SFA leaded to a decrease in the ratio of UFA [25]. The decrease in C18:1 trans-9 and C18:2 cis-6 might be related to the hydrogenation of rumen microorganisms, which could reduce the toxicity of UFA [26].…”
Section: Discussionmentioning
confidence: 98%
“…were decreased. The increase in SMCFA might due to the increase in the concentration of acetate and butyrate in the rumen, which are the substrates for de novo synthesis of milk FA by mammary epithelial cells [25], while about half of the C16:0 and other long-chain FA in milk fat are directly absorbed from blood lipids [25]. On the other hand, the results of metabolomics in our study revealed that the supplementation of inulin signi cantly downregulated the lipid metabolism in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…40%) and the uptake from circulation of preformed FA in blood (ca. 60%) (Cozma et al, 2013). More specifically, MT: synthesize short-and medium-chain FA using acetate and 3-hydroxybutyrate in the present of two key enzymes, acetyl-Co A carboxylase (ACACA) and fatty acid synthatase (FASN), and uptake FA from the plasma with the involvement of lipoprotein lipase (LPL) (Harvatine et al, 2009;Shingfield et al, 2010).…”
Section: Introductionmentioning
confidence: 99%